SOCIAL VALUES IN “GARONTO’ PASSURA’” (SEMIOTIC ANALYSIS) - Nelson Nelson; Aris Kaban Sendana; Sushy Teko Patanduk (Teaching English as a Foreign Language Overseas Journal, 2022)
The objectives of the research is to find out the social values implied in garonto’ passura’. In analyzing the data of this research, the research employed qualitative method, semiotic approach of Pierce triadic theory. The subjects of this research were engrever of Toraja traditional house, Toraja traditional guide, Toraja cultural observer and Toraja cultural activist. The data of this research were collected by observation, interview and documents analysis. The obtained data were analyzed data transcript, reduction, classified, transcribed. The results of this research from garonto’ passura’ is a prayer and aspiration of the owner of Tongkonan for the present and future. Moreover, the carving pattern found on tongkonan symbolizes social status Toraja peope based on the results of research and discussion, conclusions can be drawn that the engraving depict symbols of objects and creatures in Toraja people’s life. The message implied in the tongkonan engraving is a philosophy Toraja people’s life itself.